Заметки по фауне и систематике сверчков (Orthoptera, Gryllidae) Крыма - Горохов, А.В. (Вестник зоологии, 1984)
Faunistic and Systematic Notes on Gryllidae (Orthoptera) of the Crimea. GoroKhov A. V.— Vestn. zool., 1984, No. 1. The subfamily and tribe rank substantiation for Gryllomorphinae, Gryllomorphini and Petaloptilini. Gryllomorpha_(Gryllomorphella subgen. n) miramae Medv. and Stenonemobius bicolor (Sauss.), comb. n. are for the first time shown for the Crimea (the last also for the USSR). Mogoplistes squamiger (Fisch) is confirmed to occur in the Crimea and USSR. The new synonymy is established: Discoptila fragosoi (Bol) = Discoptila brevis B.-Bien. syn. n.; Myrmecophilus hirticaudus F.-W. = Myrmecophila pontica Mir. syn. n.= Myrimecophila tatarica Karaw, syn. n.